IMPLEMENTASI ALGORITMA BASE64 PADA SISTEM LOGIN MENGGUNAKAN JSON WEB TOKEN (JWT) UNTUK AUTENTIKASI WEB - Ulil Asyhar; Budi Hartono; Toni Wijanarko Adi Putra (UNIVERSITAS STEKOM, 2026)
Authentication security is a crucial aspect of web application development, particularly in login systems that function as the primary gateway to an application or web service. The authentication process plays a vital role in ensuring that only authorized users can access the system, thereby preventing data breaches, information misuse, and potential system damage. Traditional login methods that store passwords in plain text or rely solely on session IDs are vulnerable to theft and session hijacking. This research proposes the implementation of JSON Web Tokens(JWT) with Base64 encoding, integrated through Web Service technology, to enhance login system security. JWT is a JSON-based token standard used for secure information exchange between clients and servers. The token consists of three parts—header, payload, signature—each encoded using Base64URL. Base64 is an encoding method that converts binary data into ASCII text, making it safe for transmission over HTTP protocols. In this implementation, the bcrypt algorithm is utilized for password hashing, ensuring that the original password is never stored directly in the database. The Web Service acts as an intermediary for communication between the client and server without the need to store session data on the server. During login, the system verifies credentials, generates a JWT token, and sends it to the client for subsequent authenticated requests. Testing results demonstrate improved security, as tokens can be verified without maintaining server-side sessions, while Base64 encoding ensures safe data transmission. This implementation is expected to serve as a practical solution and reference for future advancements in web application security.